Strengthening of the oral tradition of the Puinave ethnic group in children using didactic strategies - Ducuara, Carol katherine
This project arose from the need to promote the importance of the oral tradition of the Puinaveethnic group, especially for children and young people, since they are the generation that willbe able to keep this knowledge in mind in order to preserve it and continue transmitting it.Some factors such as indirect or passive acculturation have been weakening or generatingthat young people, due to the digital age, are forgetting all these stories or no longer giveit importance and later in the future most will not speak or know the stories of the peoplePuinave. And it does not only happen with this ethnic group but with all the indigenous ethnicgroups of our department